Problems of Implementation the Inquiry Learning Model in Arabic Language Learning (A Comparative Literature Study between Indonesia and Malaysia) - Akhmad Aufa Syukron; Akhmad Zaeni; Mohamad Nor Amin Samsun Baharun (ALSINATUNA, 2025)
This study analysis the problems of the implementation of the inquiry learning model in Arabic language learning in Indonesia (Madrasah Tsanawiyah) and Malaysia (Sekolah Agama Bantuan Kerajaan) through a comparative literature study based on content analysis. Data were obtained from scientific journals related to the inquiry learning model in Arabic language learning and journals, books, and policies published 2010-2024. The results showed multidimensional problems in both countries: (1) Teachers: low mastery of inquiry methodology and Arabic; (2) Students: low basic language skills and passive learning habits; (3) Linguistics: the complexity of Arabic grammar and the interference of the mother tongue; (4) Resources: limited time allocation and inadequate facilities. Integrative solutions include: intensive and practical teacher capacity building through Indonesia-Malaysia hybrid teacher training, adjustment of learning models and approaches using guided inquiry, use of technology and development of learning resources, preparation of students and creation of learning climate, adjustment of evaluation systems and supporting policies. It can be concluded that the success of the inquiry requires a holistic approach based on the local reality of each country.